Aplicación web para el control del faenamiento de aves en la empresa Reproavi Cia.Ltda. - Mainagueza Cruz, Jefferson Alexander (2024)
This work presents the development of a web application to optimize the control and registration of poultry slaughtering at REPROAVI CIA. LTDA. Given the growth of the poultry industry and the need to implement innovative technologies, the importance of overcoming the limitations of traditional registration and control methods in the company was identified. The project focuses on addressing the resistance to modern technologies at REPROAVI by developing a technological solution that overcomes the limitations of manual registration processes. These traditional processes, based on paper sheets and Excel files, present problems of redundancy, errors in data entry, transcription, and manipulation, which affect the precision and efficiency of slaughter control. To solve these problems, a web application was implemented that automates the registration of bird weight before refrigeration, improving data accuracy and reliability. The Extreme Programming (XP) methodology was used for development, allowing effective adaptation to changes and new requirements. The developed web application allows precise control and analysis of the process, automating bird weight registration and providing real-time monitoring. The results show a significant improvement in data accuracy, reliability, and accessibility, optimizing both the efficiency and productivity of the process. The implementation of the system has facilitated real-time data analysis and informed decision-making, thanks to the generation of detailed reports. Additionally, the system has improved the traceability and transparency of the slaughtering process, representing a considerable advance in the management of this critical process in the company.